Development of a Generalized Strategy for Dry Beneficiation of Fine Coal over a Vibrating Inclined Deck. Issue 1 (2nd January 2016) - Chalavadi, Ganesh; Singh, Ranjeet K.; Sharma, Mamta; Singh, Ratnakar; Das, Avimanyu
Abstract : Beneficiation of coal fines of size −1.0 + 0.1 mm using an air table under controlled fluidization was investigated. Widely different feed coals with ash values ranging from 30–50% were shown to respond well to the process. Interactions among process variables towards influencing the separation performance were studied carefully to have a firm control over the process. Detailed statistical analysis of the experimental data was carried out and in-depth understanding of the process was accomplished through various statistical plots. The preferred operating regimes were identified for three different coals to achieve maximum mass yield for targeted product qualities. Flow sheets were developed for all the three coals investigated in order to obtain multiple usable products using a maximum of four stages of operation of the air table. A generalized strategy for dry cleaning of any coal with given characteristics was developed such that application potential of the air table can be enhanced.